Trace Elements Determination and Health Risk Assessment of Groundwater Quality in Southern Kaduna, Kaduna State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Groundwater contamination is a growing concern for water quality. This study examined the concentration of trace elements in groundwater and their implications to human health in Southern Kaduna, Nigeria. A stratified random sampling technique was adopted in stratifying the twelve (12) local government areas into four strata, while the sampling locations were selected using a purposive sampling technique. Fourty groundwater samples were collected, that is, twenty (20) samples from hand-dug wells and twenty (20) samples from boreholes. Furthermore, the concentrations of lead (Pb), chromium (Cr), manganese (Mn), iron (Fe), and zinc (Zn) were determined by direct aspiration into an air-acetylene flame using a Buck Scientific 235 atomic absorption spectrometer (AAS) and compared with the national drinking water quality standards (NDWQS). On the other hand, the human health risk assessment model was utilised to evaluate the health implications. The results of the analysis reveals that most of the trace elements (measured in mg/l) were within permissible limits, except for Chikun Borehole 2 (0.062), Chikun Well 5 (0.080), Sanga Well 5 (0.080), Zango Kataf Well 4 (0.062), Jaba Well 1 (0.054), and Jaba Well 5 (0.120) for Mn and Chikun Borehole 2 (2.7), Zango Kataf Borehole 2 (0.450), Zango Kataf Borehole 5 (0.400), Jaba Borehole 3 (0.300), Jaba Well 3 (0.250) for Fe. Additionally, the human health risk assessment for Cr indicates a very low likelihood of 0.0002 for cancer development due to oral exposure. Lastly, the study recommends continuous monitoring of groundwater quality and mapping contamination hotspots for targeted intervention.